Naphthalene sorption on red clay and halloysite modified by quaternary ammonium salts - Agnieszka Gładysz-Płaska; Agnieszka Lipke; Bogdan Tarasiuk; Magdalena Makarska-Białokoz; Marek Majdan (Adsorption Science & Technology)
Sorption of naphthalene on modified red clay and halloysite was carried out successfully. It was established that the process was of pseudo-second-order mechanism. The maximum sorption capacities were 9.23 mg/g and 112.79 mg/g for red clay and halloysite, respectively.